2016
DOI: 10.2118/176032-pa
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Individual Diffusion Coefficients of Solvent/CO2 Mixture in Heavy Oil With Pressure-Decay Method

Abstract: A novel methodology was developed to determine the moleculardiffusion coefficient for each component of the solvent/CO 2 mixture in heavy oil under reservoir conditions on the basis of the pressure-decay theory. Experimentally, molecular-diffusion tests for the solvent/CO 2 /heavy-oil systems (i.e., pure-CO 2 /heavy-oil system, C 3 H 8 /CO 2 /heavy-oil system, and n-C 4 H 10 /CO 2 /heavy-oil system) are performed with a DBR pressure/volume/temperature system at constant temperature and decayed pressure. Theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 17 publications
0
64
0
Order By: Relevance
“…(4) The extraction effect of CO2 on oil is negligible. (The literature has reported that the extraction effect of CO2 on hydrocarbons that are heavier than C9 is tiny [56], and Figure 1 shows that it is reasonable to ignore extraction in this study.) (5) The convection flow caused by the density difference is ignored.…”
Section: Diffusion Model In Porous Mediamentioning
confidence: 88%
See 2 more Smart Citations
“…(4) The extraction effect of CO2 on oil is negligible. (The literature has reported that the extraction effect of CO2 on hydrocarbons that are heavier than C9 is tiny [56], and Figure 1 shows that it is reasonable to ignore extraction in this study.) (5) The convection flow caused by the density difference is ignored.…”
Section: Diffusion Model In Porous Mediamentioning
confidence: 88%
“…Thus, it is important to simplify the calculation process with the prerequisite of ensuring a high accuracy of calculation. In this study, several pseudo-components are introduced as substitutes for all hydrocarbon components in the oil sample, which can efficiently decrease the calculation load of PR EOS without influencing the computing accuracy [56][57][58]. Specifically, in this work, hydrocarbons with a single carbon number (SCN) are lumped into three pseudo-components, which have been tested as having a good result on the oil/CO 2 system [59,60].…”
Section: Peng-robinson Equation Of State (Pr Eos)mentioning
confidence: 99%
See 1 more Smart Citation
“…Flue gas combined with n-hexane injection recovered more oil than steam alone (Li et al, 2017;Dong et al, 2015;Li and Yang, 2016). The surface tension between flue gas and heavy oil increases with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and Yang have developed a modified alpha function which combines the advantages of both the Soave-type alpha function and the logarithm-type alpha function by using a comprehensive database comprising 59 hydrocarbon and nonhydrocarbon compounds, including heavy alkanes up to n -tritetracontane ( n -C 43 H 88 ). This modified alpha function has been successfully used to more accurately predict the phase behavior of both pure substances and alkane solvent(s)–CO 2 –heavy oil systems by treating heavy oil as one pseudocomponent and multiple pseudocomponents. …”
Section: Introductionmentioning
confidence: 99%